1980
DOI: 10.1055/s-2007-996276
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Deficiency in Pigs: Changes in Food Intake and Plasma Levels of Glucose, Amino Acids, Insulin and Growth Hormone

Abstract: Pigs were fed alternately tryptophan deficient diet and the same diet supplemented with tryptophan. The deficient diet depressed food intake, caused changes in the pattern of plasma amino acids, increased plasma glucose levels and increased plasma urea levels per unit food intake. Plasma levels of insulin and growth hormone gave no indication that either hormone was involved in the suppression of food intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…Contrary to expectations, lysine deficiency (7.0 g/kg) did not increase plasma GH concentration in the present experiment. The results were in agreement with those of Montgomery et al (1980) and Roy et al (2000), who reported that dietary tryptophan and lysine deficiency had no significant effect on plasma GH. The reason could be that a single amino acid deficiency seems to have a different effect on the mechanisms regulating GH concentrations than a shortage of nutrients (Buonomo and Baile, 1990).…”
Section: Effect Of Dietary Lysine On Hormones and Glucose Concentrationsupporting
confidence: 92%
“…Contrary to expectations, lysine deficiency (7.0 g/kg) did not increase plasma GH concentration in the present experiment. The results were in agreement with those of Montgomery et al (1980) and Roy et al (2000), who reported that dietary tryptophan and lysine deficiency had no significant effect on plasma GH. The reason could be that a single amino acid deficiency seems to have a different effect on the mechanisms regulating GH concentrations than a shortage of nutrients (Buonomo and Baile, 1990).…”
Section: Effect Of Dietary Lysine On Hormones and Glucose Concentrationsupporting
confidence: 92%
“…Amino acid profiles for plasma have been published for rabbits [4], rats [7], dogs [20], pigs [18] and humans [19], Our results show little variations from the spectropho-tometric assays in any species apart from lower glutamine levels. Normal plasma leu cine and valine levels in the pig are twice those in human and rabbit plasma but other essential amino acid concentrations arc sim ilar.…”
Section: Discussionmentioning
confidence: 54%
“…Tryptophan is an essential amino acid that cannot be produced in the body. For that reason, tryptophan is well investigated and linked to feed intake in humans (Wolfe et al, 1997), cattle (Choung and Chamberlain, 1992), mice (Coskun et al, 2006) and pigs (Montgomery et al, 1980). As discussed by Koopmans et al (2006), tryptophan serves as the immediate precursor to serotonergic activity in the brain, and has been implicated in the regulation of many behavioural and physiological processes such as mood, aggression, susceptibility to stress, sleep patterns, but also the regulation of feed intake.…”
Section: Genetic Variationmentioning
confidence: 99%